The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1016/0039-6028(79)90659-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Ag(110) surface determined by using averaged leed intensities

Abstract: The constant momentum transfer averaging method has been used to determine the surface structure of the Ag(ll0) surface. A contraction of 8% of the first layer spacing compared to the bulk value is found by comparing the shape of the averaged intensity profiles with kinematic calculations rather than the position of the peaks. This result agrees well with that obtained by a multiple scattering calculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 16 publications
1
2
0
1
Order By: Relevance
“…The origin of these differences between experimental and calculated values is unclear, and we suggest that this is mostly due to temperature effects and sample preparation. This claim is supported by the calculated relaxation values for Cu (110) and Ag (110), which agree well with the experimental trend observed by LEED 83,89-92 and high-energy ion scattering (HEIS) 89 measurements for the Cu (110) surface and also by HEIS 93 measurements, shadow-cone-enhanced secondary ion mass spectroscopy (SIMS), 94 Rutherford backscattering, 95 and LEED 83 experiments for the Ag(110) surface, although earlier LEED studies [96][97][98][99] for Ag (110) reported a contraction of the first-layer spacing only. The rest of the (110) surfaces relax in a manner similar to Cu (110) and Ag (110).…”
Section: A Calculated Properties Of the Clean Surfacessupporting
confidence: 85%
“…The origin of these differences between experimental and calculated values is unclear, and we suggest that this is mostly due to temperature effects and sample preparation. This claim is supported by the calculated relaxation values for Cu (110) and Ag (110), which agree well with the experimental trend observed by LEED 83,89-92 and high-energy ion scattering (HEIS) 89 measurements for the Cu (110) surface and also by HEIS 93 measurements, shadow-cone-enhanced secondary ion mass spectroscopy (SIMS), 94 Rutherford backscattering, 95 and LEED 83 experiments for the Ag(110) surface, although earlier LEED studies [96][97][98][99] for Ag (110) reported a contraction of the first-layer spacing only. The rest of the (110) surfaces relax in a manner similar to Cu (110) and Ag (110).…”
Section: A Calculated Properties Of the Clean Surfacessupporting
confidence: 85%
“…These measurements can be correlated with the electrochemical response (representative CVs can be found in refs , ). The CVs exhibit a broad reversible feature between ∼−0.8 and −0.4 V that can be assigned to the adsorption of hydroxide anions in agreement with various in situ , ,,,, ex situ , ,,, and classical electrochemical measurements in alkaline electrolyte. The specific adsorption of hydroxide species, OH ad , is a precursor to the formation of silver oxides at potentials more positive than −0.1 V .…”
Section: Resultssupporting
confidence: 81%
“…Les effets de surface sur les milieux semi-infinis ont aussi ete analyses du point de vue theorique [11,12] et experimental [13].…”
Section: 55unclassified